Moderation of ruminal fermentation by protozoa in cattle fed high-grain diets - G. Towne; A.B. Beharka; Tiruvoor G. Nagaraja (Kansas Agricultural Experiment Station Research Reports, 1990)
Ruminal protozoa in cattle fed high-grain diets appear to contribute to the maintenance of a stable ruminal fermentation. This was evidenced by higher ruminal pH's and lower volatile fatty acid concentrations in faunated (with protozoa) than defaunated (without protozoa) cattle. The moderation of fermentation was likely due to reduced bacterial numbers associated with the presence of protozoa.
Keywords: Cattlemen' s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Acidosis; Fermentation; Protozoa; Rumen